Radar and communication spectrum sharing - Blunt, Shannon D.; Perrins, Erik Samuel, 1973- (SciTech Publishing, 2018)
The book, consisting of 23 chapters, studies radar and communication spectrum sharing by looking at systems engineering perspectives, addressing interference and considering radar/communication co-design.
Keywords: Radio frequency allocation.; elektronické knihy; electronic books